Inhibition of osteoblast activity by zoledronic acid - Basso, Fernanda Gonçalves; Turrioni, Ana Paula Silveira [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (Sociedade Brasileira de Patologia ClínicaSociedade Brasileira de PatologiaSociedade Brasileira de Citopatologia, 2013)
INTRODUCTION: Patients treated with nitrogen-containing bisphosphonates, such as zoledronic acid (ZA), have frequently shown oral bone exposure areas, termed osteonecrosis. In addition, these patients may also present low repair and regeneration potential, mainly after tooth extractions. These side-effects caused by bisphosphonates may be due to their inhibitory effects on oral mucosa and local bone cells. OBJECTIVE: To evaluate the effects of ZA on the mineralization capacity of cultured osteoblasts. MATERIALS AND METHODS: Human immortalized osteoblasts (SaOs-2) were grown in plain culture medium (Dulbecco's Modified Eagle Medium [DMEM] + 10% fetal bovine serum [FBS]) in wells of 24-well plates. After 48-hour incubation, the plain DMEM was replaced by a solution with ZA at 5 µM which was maintained in contact with cells for seven, 14 or 21 days. After these periods, cells were evaluated regarding alkaline phosphatase (ALP) activity and mineral nodule formation (alizarin red). Data were statistically analyzed by Mann-Whitney test, at 5% of significance level. RESULTS: ZA caused significant reduction on ALP activity and mineral nodules formation by cultured osteoblasts in all evaluated periods (p < 0.05). CONCLUSION: These data indicate that ZA causes inhibition on the osteogenic phenotype of cultured human osteoblasts, which, in turn, may reduce bone repair in patients subjected to ZA therapy.

INTRODUÇÃO: Pacientes em tratamento com bisfosfonatos, sobretudo com os nitrogenados, como o ácido zoledrônico (AZ), têm apresentado áreas de exposição de tecido ósseo na cavidade oral, caracterizadas como osteonecrose. Essas áreas apresentam limitada capacidade de reparo, principalmente após exodontias. Esses efeitos podem ser resultado do efeito inibitório causado por esse tipo de medicamento sobre as células da mucosa e do tecido ósseo local. OBJETIVO: Avaliar o efeito do AZ sobre a capacidade de mineralização de osteoblastos in vitro. MATERIAIS E MÉTODOS: Foi utilizada uma linhagem celular de osteoblastos humanos (SaOs-2). As células foram cultivadas em meio de cultura completo (Dulbecco's Modified Eagle Medium [DMEM] + 10% de soro fetal bovino [SFB]). Após 48 horas de incubação, o DMEM completo foi substituído por um novo DMEM sem SFB, ao qual foram adicionados 5 µM de AZ. Essa solução foi mantida em contato com as células por sete, 14 ou 21 dias. Após esse período, as células foram avaliadas quanto à atividade de fosfatase alcalina (ALP) e à produção de nódulos de mineralização (alizarin red). Os dados foram submetidos ao teste estatístico de Mann-Whitney, considerando nível de significância de 5%. RESULTADOS: A exposição das células ao AZ causou redução significativa na atividade de ALP e na formação de nódulos mineralizados em todos os períodos avaliados (p < 0,05). CONCLUSÃO: Esses resultados revelam que o AZ causa alteração inibitória no fenótipo osteogênico das células humanas em cultura, o que pode reduzir a capacidade de reparo do tecido ósseo após o contato com esse tipo de medicamento.
Inibição da atividade de osteoblastos expostos ao ácido zoledrônico
Keywords: osteonecrose; reparo; mineralização; osteoblastos; osteonecrosis; repair; mineralization; osteoblasts